Enabling Collaborative Numerical Modeling in Earth Sciences using Knowledge Infrastructure. (October 2019) - Bandaragoda, C.; Castronova, A.; Istanbulluoglu, E.; Strauch, R.; Nudurupati, S.S.; Phuong, J.; Adams, J.M.; Gasparini, N.M.; Barnhart, K.; Hutton, E.W.H.; Hobley, D.E.J.; Lyons, N.J.; et al.
Abstract: Knowledge infrastructure is an intellectual framework for creating, sharing, and distributing knowledge. In this paper, we use knowledge infrastructure to address common barriers to entry into numerical modeling in Earth sciences as demonstrated in three computational narratives: physical process modeling education, replicating published model results, and reusing published models to extend research. We outline six critical functional requirements: 1) workflows designed for new users; 2) community-supported collaborative web platform; 3) distributed data storage; 4) software environment; 5) personalized cloud-based high-performance computing platform; and 6) a standardized open source modeling framework. Our methods meet these functional requirements by providing three interactive computational narratives for hands-on, problem-based research using Landlab on HydroShare. Landlab is an open-source toolkit for building, coupling, and exploring two-dimensional numerical models. HydroShare is an online collaborative environment for the sharing of data and models. We describe the methods we are using to accelerate knowledge development by providing a suite of modular and interoperable process components that allows students, domain experts, collaborators, researchers, and sponsors to learn by exploring shared data and modeling resources. The system is designed to support uses on the continuum from fully-developed modeling applications to prototyping research software tools. Landlab notebooks are available for interactive computing on HydroShare athttps://doi.org/10.4211/hs.fdc3a06e6ad842abacfa5b896df73a76 and for further development on Github athttps://zenodo.org/badge/latestdoi/187289993 . Highlights: Knowledge Infrastructure can address common challenges to using online systems for collaborative numerical modeling. Advanced cyberinfrastructure coupled with research software community support for more efficient Earth system science. Three computational narratives using Landlab on HydroShare replicate and reuse Earth surface models for education.